1980
DOI: 10.1002/ijch.198000020
|View full text |Cite
|
Sign up to set email alerts
|

Theory of Magnetic Susceptibilities and NMR Chemical Shifts in Terms of Localized Quantities

Abstract: A coupled Hartree–Fock theory for diamagnetic susceptibilities χ and chemical shifts σ in terms of localized MO's and individual gauge origins for the different MO's is derived. The new coupled Hartree–Fock equations and expressions for χ and σ differ from the traditional ones by the presence of “exchange coupling terms” (ECT) and “resonance coupling terms” (RCT). For the ECT, that are expected to be very small, a simple approximation is proposed. Both the ECT and the RCT can be decomposed into “diamagnetic” a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
325
0
4

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 675 publications
(332 citation statements)
references
References 25 publications
3
325
0
4
Order By: Relevance
“…60 The latter complexes, however, show a specific behaviour for the metal-bound carbons, which can be attributed to anisotropic effects. [61][62][63] In our series of compounds, linear regression of the calculated charges in 1a-c 64 and experimental NMR measurements ( Figure 4) also yields an appreciable fit (R 2 = 0,91 -see supporting information). We therefore assume that the 13 C NMR data of the heterocyclic carbons that are not bound to the metal offer a qualitative probe for the partial charge (re)distributions during complex formation.…”
Section: C) Nmr Spectroscopic Characterizationsupporting
confidence: 55%
“…60 The latter complexes, however, show a specific behaviour for the metal-bound carbons, which can be attributed to anisotropic effects. [61][62][63] In our series of compounds, linear regression of the calculated charges in 1a-c 64 and experimental NMR measurements ( Figure 4) also yields an appreciable fit (R 2 = 0,91 -see supporting information). We therefore assume that the 13 C NMR data of the heterocyclic carbons that are not bound to the metal offer a qualitative probe for the partial charge (re)distributions during complex formation.…”
Section: C) Nmr Spectroscopic Characterizationsupporting
confidence: 55%
“…While the origin dependence is usually small as long as sufficiently large basis sets are used, we have checked the sensitivity of the results with respect to the origin. We found that on GGA level the center of the electron charge gives practically the same values as calculations using the fully invariant IGLO (individual gauges for localized orbitals) 38 procedure (which, however, is not rigorous for hybrid functionals) and used this point as the origin for our calculations. Table I shows the obtained principle values of the g-tensor and the hyperfine matrix in comparison with previous theoretical results and experiment.…”
Section: Resultsmentioning
confidence: 79%
“…There have been many measurements of the chemical shifts [60][61][62] of carbon and protons in norbornane, examples of which are the work of Abraham and co-workers 60 and Lippmaa et al 61 We used the localized orbital/local origin ͑LORG͒, 63 C chemical shifts than the IGLO method, particularly for the proton spectrum. However, it appears that when a correlated wave function is used, the GIAO approach provides the best agreement with experiment.…”
Section: Nmr Propertiesmentioning
confidence: 99%